Challenge of contemporary terrorism: tackling roots via education - Desker, Barry (2016)
Recent massacres by terrorists in Brussels and Lahore reflect the changing dynamic of the threat. Fear of attacks forces governments to divert resources to combat possible threats in ungoverned zones and areas of sectarian conflict.